Impact of COVID-19 Pandemic on Nutrition Services in Banyumas, Central Java - Ihsani, Arina Nurul; Achadi, Endang L.; Pratiwi, Rany Sekar (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The current COVID-19 pandemic and social restriction led to disruptions to Indonesia’s public health services. This research assessed the pandemic impact on nutrition services in Banyumas regency. Utilizing monthly registers from 40 subdistrict health services and interviews with public health officers, this research is a mixed-method study. Paired sample t-test was performed to compare the changes before and during the pandemic. Reduced community-based growth monitoring activities (p = 0,001), and early initiation of breastfeeding (p = 0,03) were two nutrition challenges identified in Banyumas. A slight reduction in postpartum vitamin A supplementation, antenatal care 1 and 4 services were also observed but statistically non-significant. Knowing that good nutrition strengthens the immunity and overall health of mothers, babies, and families. Improving nutrition services as part of the public health system and adaptive public policy is key to building resilience to future pandemics.